1998
DOI: 10.1128/mcb.18.1.240
|View full text |Cite
|
Sign up to set email alerts
|

DDB, a Putative DNA Repair Protein, Can Function as a Transcriptional Partner of E2F1

Abstract: The transcription factor E2F1 is believed to be involved in the regulated expression of the DNA replication genes. To gain insights into the transcriptional activation function of E2F1, we looked for proteins in HeLa nuclear extracts that bind to the activation domain of E2F1. Here we show that DDB, a putative DNA repair protein, associates with the activation domain of E2F1. DDB was identified as a heterodimeric protein (48 and 127 kDa) that binds to UV-damaged DNA. We show that the UV-damaged-DNA binding act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 73 publications
5
97
0
Order By: Relevance
“…It has previously been shown that DDB2 interacts with E2F1 and together with DDB1, stimulates E2F1-activated transcription (Hayes et al, 1998;Shiyanov et al, 1999, also reviewed by Tang and Chu, 2002). Our results support the hypothesis that in untransformed primary mouse epithelial cells, activation of DDB2 by E2F could be critical for the regulation of the G1/S transition.…”
Section: Ddb2 and Transcriptionsupporting
confidence: 90%
“…It has previously been shown that DDB2 interacts with E2F1 and together with DDB1, stimulates E2F1-activated transcription (Hayes et al, 1998;Shiyanov et al, 1999, also reviewed by Tang and Chu, 2002). Our results support the hypothesis that in untransformed primary mouse epithelial cells, activation of DDB2 by E2F could be critical for the regulation of the G1/S transition.…”
Section: Ddb2 and Transcriptionsupporting
confidence: 90%
“…In addition to transcriptionally regulating DNA repair genes, E2F1 also physically associates with a number of DNA repair proteins including DDB2, NBS1 and TopBP1 (Hayes et al, 1998;Maser et al, 2001;Liu et al, 2003). E2F1 has also been shown to colocalize with BRCA1 in foci that are presumptive sites of DNA repair .…”
Section: E2f1 Regulation Of Dna Repairmentioning
confidence: 99%
“…These include transcriptional upregulation of DNA repair factors such as DDB2 and XPC (Adimoolam and Ford, 2002;Amundson et al, 2002;Tan and Chu, 2002;Fitch et al, 2003), recruitment of repair factors to sites of DNA damage through physical interaction with p53 (Wang et al, 2003) and the ability of p53 to function as a chromatin accessibility factor to allow access of repair factors to sites of damage (Rubbi and Milner, 2003). Given that E2F1 can upregulate the expression of a number of DNA repair genes (Wang et al, 1999;Polager et al, 2002;Ren et al, 2002) and that E2F1 physically associates with several DNA repair factors (Hayes et al, 1998;Maser et al, 2001;Liu et al, 2003), it is quite possible that like p53, the antiapoptotic effect of E2F1 is related to a stimulation of DNA repair.…”
Section: E2f1 Regulation Of Apoptosismentioning
confidence: 99%
“…In addition to its role in DNA repair, DDB2 has been also implicated in transcription. DDB2 associates with the transcriptional activator protein E2F1 (Hayes et al, 1998). Moreover, DDB2 also associates with the transcriptional coactivator proteins CBP/p300 and the STAGA complex (Datta et al, 2001;Martinez et al, 2001).…”
Section: Introductionmentioning
confidence: 99%